2004
DOI: 10.1111/j.1365-2133.2004.06197.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy using meta-tetrahydroxyphenylchlorin (FoscanR) for the treatment of vulval intraepithelial neoplasia

Abstract: This small case series demonstrates that mTHPC-PDT is a useful initial treatment for VIN III. It is relatively selective, shows good cosmesis and conserves form and function. This is a major advantage over surgery. Repeat treatments are also possible, which is important in a condition such as VIN, which tends to be multifocal. Systemic mTHPC-PDT appears to have an advantage over topical 5-aminolaevulinic acid-PDT as the photosensitizer is distributed widely in areas of disease and consequently identifies foci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 11 publications
0
28
0
1
Order By: Relevance
“…Surgical excision can be mutilating and a technique like PDT, which has the potential to destroy the disease process with healing by regeneration of normal tissue rather than with significant scarring, is a most attractive option. Pilot clinical studies of PDT have been undertaken for all these conditions, with promising results, but full clinical trials are now needed to establish for which ones PDT might become the treatment of choice [34,35]. In theory, pre-cancers or early cancers of any solid or hollow organ may be suitable for PDT, but for this to become a realistic option, studies must be done to establish how the normal organ in which these lesions arise will respond to PDT and that the treatment will not lead to any unacceptable changes in structure or function at any time during healing.…”
Section: (Xi) Breastmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical excision can be mutilating and a technique like PDT, which has the potential to destroy the disease process with healing by regeneration of normal tissue rather than with significant scarring, is a most attractive option. Pilot clinical studies of PDT have been undertaken for all these conditions, with promising results, but full clinical trials are now needed to establish for which ones PDT might become the treatment of choice [34,35]. In theory, pre-cancers or early cancers of any solid or hollow organ may be suitable for PDT, but for this to become a realistic option, studies must be done to establish how the normal organ in which these lesions arise will respond to PDT and that the treatment will not lead to any unacceptable changes in structure or function at any time during healing.…”
Section: (Xi) Breastmentioning
confidence: 99%
“…PD is an approved technique for guiding glioma resection during open surgery (as discussed under brain tumours) and also for guiding endoscopic resection of dysplastic (pre-cancerous) areas in the bladder [11,34].…”
Section: (Xiii) Photodiagnosismentioning
confidence: 99%
“…The efficacy of Foscan s -PDT in the treatment of early squamous cell carcinoma Lou et al, 2004) and other malignancies has also been recently reported (Campbell et al, 2004;Lovat et al, 2005;Shikowitz et al, 2005). Endoplasmic reticulum and Golgi apparatus have been demonstrated as preferential sites of Foscan s accumulation in cultured tumour cells after 3-h incubation (Teiten et al, 2003a) leading to primary photodamage of these organelles upon irradiation (Teiten et al, 2003b).…”
mentioning
confidence: 99%
“…124 After multiple sessions, ALA PDT can achieve long-term results lasting several months and years in some 60% of patients. Although other systemic PSs have been used in a small number of patients, 127 the results are not consistent or sufficiently reproducible and there is the inconvenience of skin photosensitivity.…”
Section: Vulvar Intraepithelial Neoplasiamentioning
confidence: 99%